Are Ionic Liquids Better Extracting Agents Than Toxic Volatile Organic Solvents? A Combination of Ionic Liquids, Microwave and LC/MS/MS, Applied to the Lichen Stereocaulon glareosum - Calla-Quispe, Erika; Robles, Juana; Areche, Carlos; Sepulveda, Beatriz (Frontiers in Chemistry, 2020)
We report a green strategy for the extraction of lichen substances from Stereocaulon glareosum. This sustainable alternative does not use volatile toxic organic solvents, but it is assisted by microwave and is checked by UHPLC/ESI/MS/MS. Ionic liquids may provide a better alternative in the extraction of natural products from lichens.